A cross sectional study to find out the efficacy of prevention of parent to child transmission services providing centers of Indore division - Jain, Chakresh; Khatri, A. K.; Yesikar, Veena; Dixit, Sanjay; Rai, Shailesh (International Journal Of Community Medicine And Public Health, 2017)
Background: The HIV and AIDS epidemic is not just a public health concern, but a major socio-economic problem in India as it is in other parts of the world. In India PPTCT interventions under NACP was started in2002, using single dose NVP prophylaxis For HIV positive pregnant women during labour & also for her new born child immediately after birth. The objective of the study was to find out the proportion of HIV among ANC registered & the efficacy of PPTCT by determining seroconversion rate in children born to HIV positive mothers during study period. Methods: All PPTCT Services providing centres located in four districts of Indore division were taken in study. The required information (data of 1st January to 31st December 2014) was collected through pre-designed semi structured questionnaire undertaken nodal in charge, counselling staff/ laboratory technicians of each centre during the study period of January to October 2015. The data collected was entered into Microsoft excel spread sheet and analysis was done by SPSS. Results: The number of HIV positive registered ANC cases & positivity rate among them, both were highest at medical college level as they are catering highest numbers of ANC OPDs & referral too while it is lowest at CHCs level. Among total 67 positive pregnant women, two babies died before 6 weeks. Out of 65 babies tested & 2(3%) babies were found positive. Conclusions: There has been an improvement in number of pregnant women undergoing HIV testing with appropriate pre-test & post-test counselling over years but ANC load in hospitals of urban areas, were higher in comparison to rural, so up gradations of hospitals at primary level should be done.